Icariin attenuates titanium particle‐induced inhibition of osteogenic differentiation and matrix mineralization via miR‐21‐5p. (26th March 2018) - Lian, Feng; Zhao, Chengbin; Qu, Jing; Lian, Yongyun; Cui, Yong; Shan, Liang; Yan, Jinglong
Abstract: Inhibition of bone regeneration by wear debris is the main cause of peri‐prosthetic osteolysis. Here, we investigated the effect of icariin on cell proliferation, apoptosis, osteogenic differentiation and matrix mineralization of osteoblasts in an in vitro model of titanium (Ti) particle‐induced osteolysis. In the present study, MC3T3‐E1 cells were pretreated with 10 −8  M icariin for 4 h and then incubated with Ti particles (0.1 mg/mL). The results showed that Ti particles inhibited cell proliferation and promoted cell apoptosis of MC3T3‐E1 cells, whereas icariin pretreatment blocked the effect of Ti particles. In addition, we found that icariin stimulation alone increased ALP activity, accelerated matrix mineralization and upregulated the levels of bone morphogenetic protein 2 (BMP2), Runt‐related transcription factor 2 (Runx2), osteocalcin (OCN) and miR‐21‐5p; whereas, Ti particles alone exerted the opposite effects. Icariin partly reversed the effect of Ti particles on cell differentiation and mineralization. Twenty hours after transfection with antagomiR‐21‐5p or antagomiR‐NC, the cells were pretreated with icariin for 4 h and then incubated with Ti particles. Further studies showed that partial knockdown of miR‐21‐5p abolished the promotion effect of icariin on osteoblast differentiation and matrix mineralization in Ti particle‐stimulated MC3T3‐E1 cells. In conclusion, miR‐21‐5p may be a potential pro‐osteogenesis regulator and icariin may protect against Ti particle‐induced inhibition of osteogenic differentiation and mineralization through upregulation of miR‐21‐5p.